Polarization in BRICS and G7: Scopus-Indexed Journal Production Trends (2013–2023) - Eungi Kim; Sureshkrishnan Ramakrishnan; Jason Lim Chiu (Publications)
The objective of this study is to examine disparities in Scopus-indexed journal production between BRICS and G7 countries from 2013 to 2023, focusing on growth trends, open access (OA) and non-OA production, subject representation, and quality metrics. Using data from the SCImago Journal Rank portal, the analysis evaluated growth rates, quartile rankings, and publisher dynamics. G7 countries maintained their global leadership, characterized by stable production systems and high-impact journals predominantly managed by commercial publishers. In contrast, the countries of Brazil, Russia, India, China, and South Africa (BRICS) exhibited diverse trends: China and Russia demonstrated rapid expansion through state-backed initiatives and the rise of domestic publishers, aiming to reduce reliance on foreign publishers and enhance global visibility. However, India experienced a decline, while Brazil and South Africa showed only modest growth in Scopus-indexed journal production. Similarly, G7 countries displayed internal variability, with the UK and Italy achieving notable growth, whereas Japan and France faced declines. These disparities within both groups underscore the critical influence of national research policies and infrastructure on journal production. BRICS countries showed a strong focus on STEM disciplines, with China emerging as a leader in both OA and non-OA journal production. Conversely, G7 countries maintained a balanced representation across STEM and social sciences. These findings suggest that national policies and infrastructure investments are key drivers of journal production growth, with BRICS countries leveraging new initiatives for expansion and G7 countries maintaining dominance through established systems.